Analysis Of The Difference Of Color Fly Grill To Flat Density In Tanjung Perak Temporary Waste Disposal Surabaya - Lailatul Fitria, Siti; Aan Adriansyah, Agus; Handayani, Dwi (PROCEEDING SURABAYA INTERNATIONAL HEALTH CONFERENCE 2019, 2020)
The port is the largest level of mobilization so that the potential for disease transmission and the risk of becoming a suitable habitat as a place for breeding disease vectors include flies. Flies are insects that have a sensitivity to certain color differences but not all colors can be recognized. This study aims to analyze the differences in the color of the fly grill against the density of flies at Tanjung Perak TPS Surabaya. This type of research is a quasi-experiment with approach cross-sectional. The population of the study was all fly species in Tanjung Perak TPS Surabaya. The research sample was taken by cluster random sampling technique with a sample size of 6 repetitions. Data analysis with the Kruskal Wallis test. The results of this study indicate that there are at least a pair of colors fly grill that has significant color differences in fly density with a significant value of 0.039 (ρ <α). The order of the color of fly grill the most preferred until it is not liked by flies is yellow, red, white and blue. The conclusion of this study is that there is a significant difference in color to fly grill fly density, and the color of the fly grill most preferred by flies is yellow and the color that is least preferred by flies is blue. The advice given is to repaint the blue color in the building of the trash or container that has been corrosive, garbage transportation is carried out routinely.